The Effect of Edmodo-Based Blended Learning on Students' Achievement - Jesi Jecsen Pongkendek; Evy Nurvitasari; Ardi Firmansyah (Universitas Negeri Malang, 2021)
Blended learning is a mixed learning model that combines online and face-to-face learning that utilizes a website or application that can be accessed with a smartphone, laptop, or computer connected to the internet network. Blended learning is an alternative learning model applied during the Covid-19 pandemic. This study aims to determine the effect of the Edmodo-based blended learning model on student learning outcomes. This type of research is pre-experimental with one group pretest-posttest design. The research was conducted at SMAN 1 Kurik with Class XI MIPA 1, which consisted of 26 students as the research sample. Research data was obtained in learning outcomes data conducted at the beginning and end of learning. Student learning outcomes data were analyzed parametrically with paired sample t-test. Based on the results of the study, it was obtained that students' learning completeness was 85%, N-Gain was 0.56 (medium category), and t-count was 20.79 (t-count > t-table). Through this research, it can be concluded that there is an influence of the Edmodo-based blended learning model on the chemistry learning outcomes of students in class XI MIPA 1 SMAN 1 Kurik. REFERENCES Albiladi, W. S., & Alshareef, K. K. (2019). Blended Learning in English Teaching and Learning : A Review of the Current Literature. 10(2), 232-238. https://doi.org/http://dx.doi.org/10.17507/jltr.1002.03 Angraini, M. R., Muharini, R., & Lestari, I. (2018). Penerapan Blended Learning Berbasis Edmodo Terhadap Minat Dan Hasil Belajar Siswa SMAN 9 Pontianak. 1-12. Ariyatun, A., & Octavianelis, D. F. (2020). Pengaruh Model Problem Based Learning Terintegrasi Stem Terhadap Kemampuan Berpikir Kritis Siswa. JEC: Journal of Educational Chemistry, 2(1), 33. https://doi.org/10.21580/jec.2020.2.1.5434 Basuki, A. R. R. ismet. (2018). Pengaruh Model Pembelajaran Blended Learning Didukung E-Learning ( Edmodo , Schoology ) Dan Motivasi Berprestasi Terhadap Kompetensi Siswa Pada Mata Pelajaran Instalasi Motor Listrik Di SMK PGRI 1 Surabaya. 3, 193-200. Chaeruman, U. A. (2013). Merancang Model Blended Learning. 399-409. Daulay, U. A., & Manurung, B. (2016). Pengaruh Blended Learning Berbasis Edmodo dan Motivasi Belajar Terhadap Hasil Belajar IPA Biologi dan Retensi Siswa pada Sistem Peredaran Darah Manusia di Kelas VIII SMP Negeri 5 Medan. 6(1), 260-266. Ekayati, R. (2018). Implementasi Metode Blended Learning Berbasis. 4(2), 50-56. Fitriana, N. (2017). Mata Kuliah Pemisahan Kimia Materi Kromatografi Untuk Meningkatkan Kualitas Belajar. 4, 46-54. Fitriani, R. S. (2019). Model Pembelajaran Berbasis Saintifik Menggunakan Alat Peraga E Pen Interaktif dengan Muatan Kearifan Lokal pada Era Industri 4 . 0 untuk Pengajaran BIPA di Uninus. 6(2), 40-46. https://doi.org/10.33603/dj.v6i2.2187 Harjono, H. S. (2013). Literasi Digital: Prospek dan Implikasinya dalam Pembelajaran Bahasa. 53(9), 1689-1699. https://doi.org/10.1017/CBO9781107415324.004 Harta, J., Limbong, S. A., & Waruwu, E. E. (2020). Pengembangan Media Pembelajaran Asam Basa Inovatif Berbasis Green Labyrinth untuk SMA. J-PEK (Jurnal Pembelajaran Kimia), 5(1), 17-31. https://doi.org/10.17977/um026v5i12020p017 Husna, Ikhsan, M., & Fatimah, S. (2013). Peningkatan Kemampuan Pemecahan Masalah Dan Komunikasi Matematis Siswa Sekolah Menengah Pertama Melalui Model Pembelajaran Kooperatif Tipe Think-Pair-Share (Tps). 1(2), 81-92. Istiqomah. (2019). Pembelajaran Menulis Karangan Deskripsi Dengan Model Kooperatif Tipe STAD Terhadap Siswa Kelas X Man 3 Aceh Utara. 19(2), 216-235. Khoiroh, N., Munot, & Lilik, A. (2017). Pengaruh Model Pembelajaran Blended Learning Dan Motivasi Belajar Terhadap Hasil Belajar Siswa. 10, 97-110. Lazem, S. (2019). On Designing Blended Learning Environments for Resource-Challenged Communities. 14(12), 183-193. https://doi.org/https://doi.org/10.3991/ijet.v14i12.10320 Shaimaa Surat Edaran Nomor 4 Tahun 2020 Tentang Pelaksanaan Kebijakan Pendidikan Dalam Masa Darurat Penyebaran Corona Virus Disease(COVID-19), (2020). Murti, H. W. (2019). Kajian Industri 4.0 Untuk Penerapannya Di Indonesia. Jurnal Manajemen Industri Dan Logistik, 01, 1-13. https://doi.org/10.30988/jmil.v3i1.59 Nasrullah, R., Aditya, W., Satya, T. I., Nento, M. N., Hanif, N., Miftahussururi, & Akbari, Q. S. (2017). Literasi Digital. Kementerian Pendidikan dan Kebudayaan. Pongkendek, J. J., Parlindungan, J. Y., & Marpaung, D. N. (2019). Effectiveness of the Application of Team Games Tournament Cooperative Learning Model (TGT) to Improve Learning Outcomes of Students of Class XI Science 1 SMA Frater Makassar in the Principal Material of Salt Hydrolysis. IOP Conference Series: Earth and Environmental Science, 343(1). https://doi.org/10.1088/1755-1315/343/1/012228 Pongkendek, Jesi Jecsen, Marpaung, D. N., Nurvitasari, E., & Parlindungan, J. Y. (2021). The Use Of Chemsketch to Increase Student Learning Outcomes and Motivation in Learning Hydrocarbons. J-PEK (Jurnal Pembelajaran Kimia), 6(1), 9-18. https://doi.org/http://dx.doi.org/10.17977/um026v6i12021p009 Subagiyo, S. (2019). Penerapan Model Blended Learning untuk meningkatkan Pemahaman Konsep Termokimia Siswa. Journal of Educational Chemistry (JEC), 1(1), 1. https://doi.org/10.21580/jec.2019.1.1.3830 Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Alfabeta. Surjaman, T. (2017). Penilaian Hasil Proses Belajar Mengajar. Remaja Rosdakarya. Werang, B. R. (2012). Belajar dan Pembelajaran. Elang Mas. Werang, B. R. (2015). Pendekatan Kuantitatif dalam penelitian sosial. Calpulis.